Mild neurocognitive disorder and mood disorder: Possible relationships - Tassoni, Lúrya Marcela Lopes Bertoluzzi; Borges, Karina Kelly; Zaniratto, Jayne (Seven Editora, 2024)
Introduction. While depressive symptoms may represent a primary mood disorder, they may also reflect early signs of cognitive decline. Goal. To evaluate the possible relationships between Mild Neurocognitive Disorder (NLD) and Mood Disorder. Method. This is an exploratory, descriptive study with a quantitative approach, in which 19 medical records were analyzed with results of patients with a clinical diagnosis of TNL through clinical analysis data (medical consultations and laboratory tests and neuropsychological evaluation), between August 2018 and August 2019. The instruments used were a structured interview, Mini Mental State Examination (MMSE), Picture Memory Test (FMT), Semantic Verbal Fluency Test (Animal Category), Proverbs, Clock Drawing Test (TDR), Geriatric Depression Scale (GDS) and Geriatric Anxiety Inventory (GAI). Findings. Of the 19 patients, they had a mean age of 74.36±1.31 (66-88) years and a mean education of 2.26±0.37 (0-4) years.  There was a significant correlation between the mean MMSE and RDT, Proverbs and GAI, thus showing the worse cognitive performance, worse results in metalanguage and greater anxiety symptoms. There was also significant evidence between GDS and GAI, showing correlation between symptoms and their severity, with clinical intensity for anxiety (M=12.00±1.14). Conclusion. Mood disorders suggest neurocognitive impairments, which may contribute to or aggravate symptoms related to TNL, such as impairments associated with memory. DOI:https://doi.org/10.56238/sevened2024.018-028